Avaliação de famílias de pacientes em situação de terminalidade sob cuidados paliativos: estudo à luz do Modelo Calgary - Rodrigues, Francileide de Araújo (2016)
palliative care are presented as a therapeutic modality with an interdisciplinary approach, to be accomplished for the benefit of the patient, because it consists of a set of actions that aim to improve the quality of life and dignity of patients in treatment or in terminality process and their families with the diagnosis of a terminal disease, including counseling and support to mourning. The choice of the Calgary Model as theoretical basis for this study is due to the fact of integrating the structural, developmental and functional dimension, which allows a view of family dynamics in order to improve the planning of care provided to those involved in this process. Objective: to evaluate the structure, development and functionality of families of patients terminally ill in hospice care in light of the Calgary Model. Methodology: this is a field of study with a qualitative approach, based on the Calgary Family Assessment Model, performed in a hospital in the city of João Pessoa, Paraíba’s state capital. The survey sample consisted of ten families. Each was represented by patients with terminal illness and a family caregiver. In compliance with the ethical observances related to research involving human subjects, recommended by Resolution 466/2012 of the National Health Council, the project was assessed and approved by the Ethics Committee of the University Hospital Research Lauro Wanderley (HULW), the Federal University of Paraíba, under CAAE nº 33261114.1.0000.5183. Data were collected in the months of August, September and October 2014. For this, we used the interview technique, the recording system unit mp4, the field diary, the Palliative Performance Scale and the recommended tools for Calgary Model: the genogram and eco-map. The empirical material was analyzed qualitatively, in the light of the Calgary Model. Results: the results enabled the development of two articles. The first, entitled 'Assessing the structure, development and functionality of families of elderly with disease in terminal phase', in which it was possible to recognize that caring for elderly patients with end-stage disease affects the family structure and dynamics. With respect to the stages of life of families, all of them were in two stages: the family at the end of life and the children independency stage, they are getting their emancipation. The second article - 'Calgary Model Application for evaluation families of patient with terminal cancer' - enabled a holistic view of the patient's family with cancer in terminal illness of life, in which nurses may notice that each family is unique and presents dynamics of different adjustments in relation to the patient living with terminal cancer. It was found that most families is characterized as an extensive female single parent and overload of women in the family's role as caregiver. Conclusion: the survey results will support the planning of nursing care through the full evaluation of the family, and provide care which main focus is the quality of family life with a view to assist the group to comprehend own resources to deal the difficulties surrounding the family of patient with disease in late life stage.